Periodicals on Islam in South Africa - Haron, Muhammed (Bulletin on Islam and Christian-Muslim relations in Africa, 1988)
The article contains a list of 80 periodicals on Islam and concludes with a brief analysis of the list looking at unique periodicals, editors/contributors, current contributions, contents, quality and statistics. (DÜI-Ott)